Bank performance, efficiency and ownership in transition countries - John P. Bonin; Iftekhar Hasan; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
Using data from 1996 to 2000, we investigate the effects of ownership, especially by a strategic foreign owner, on bank efficiency for eleven transition countries in an unbalanced panel consisting of 225 banks and 856 observations.Applying stochastic frontier estimation procedures, we compute profit and cost efficiency scores taking account of both time and country effects directly.In second-stage regressions, we take these efficiency measures along with return on assets as dependent variables with dummy variables for ownership type, a variable controlling for bank size, and dummy variables for year and country effects as explanatory variables.Methodologically, our results demonstrate the importance of including fixed effects, especially country effects, and also suggest a preference for efficiency measures over financial measures of bank performance in empirical work on transition countries. With respect to the impact of ownership, we conclude that privatization by itself is not sufficient to increase bank efficiency as government-owned banks are not appreciably less efficient than domestic private banks.Our results do support the hypothesis that foreign ownership leads to more efficient banks in transition countries.We find that foreign-owned banks are more cost-efficient than other banks and that they also provide better service, in particular if they have a strategic foreign owner. Moreover, the participation of international institutional investors is shown to have a considerable additional positive impact on profit efficiency, which is consistent with the notion that these investors facilitate the transfer of technology and know how to newly privatized banks.In addition, we find that the remaining government-owned banks are less efficient in providing services, which is consistent with the hypothesis that the better banks were privatized first in transition countries.Finally, efficiency declines with bank size, which could call into question government-orchestrated bank consolidation strategies.We conjecture that the presence of many small and efficient foreign greenfield operations in these transition countries may be responsible for this result.
URN:NBN:fi:bof-201408071909
Keywords: P30; P34; P52; 330